PENGEMBANGAN EKOWISATA BAHARI MANGROVE SEBAGAI UPAYA REGENERASI EKONOMI DI DESA BEDONO - Andi Fakhirah Anastasia; Mussadun, Mussadun (Plano Madani : Jurnal Perencanaan Wilayah dan Kota, 2025)
Urban regeneration aims to fulfill economic, environmental, and social needs. The economic aspect is a crucial part of this regeneration. Coastal areas such as Bedono Village have the potential for mangrove forest tourism, which includes the Pesona Mangrove Bedono Bangkit Tourism Track and the Moropand Mangrove Tourism Track. However, tidal flooding damages tourism infrastructure and can affect the local economy. This study aims to formulate a development strategy for marine mangrove ecotourism as an effort to regenerate the economy in Bedono Village affected by tidal flooding, using descriptive statistical and qualitative descriptive analyses. The results of the study revealed development strategies with an economic regeneration concept, including developing culinary tourism featuring local products, trekking routes, mangrove seedling planting, observation towers, and beach clean-up activities as attractions. Amenities development includes souvenir shops and public restrooms, while accessibility improvements involve building parking areas, road repairs, and boat docks. For information and promotion, the strategies include providing information on facilities and accommodations, organizing events, participating in tourism exhibitions, promoting through mass media and social media, creating tourism banners, establishing a tourism information center, and enhancing human resource quality through training in tour guiding, managing food stalls or kiosks, transportation management, and photography and videography. Long-term development includes adding new tourist attractions, elevating roads, expanding mangrove forests, implementing ecotourism development policies, and conducting monitoring and evaluation of facilities and ecotourism activities.